2020
DOI: 10.1108/add-01-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative longitudinal study of the first UK Dual Diagnosis Anonymous (DDA), an integrated peer-support programme for concurrent disorders

Abstract: Purpose Dual Diagnosis Anonymous (DDA) is a peer-led programme developed in the USA, which aims to address mental and addictive disorders in an integrated manner. This study is part of a mixed-methods evaluation of the first DDA pilot in the UK, and the purpose of this study is to explore the impact and mechanism of change of the programme through the perspective of DDA attendees, facilitators and the funding commissioners. Design/methodology/approach Six DDA members were interviewed three times over a perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…Previous research found that sense of belongingness predicts attendance and success within 12-step programs (Rice et al, 2012), while "uniqueness" shares operational features with group acceptance, which is considered an important factor for recovery in peer support programs (Repper et al, 2011). Lastly, in a previous study, DDA members reported that acceptance, social identification, and social interaction-which can be conceptualized as uniqueness, belongingness, and inclusion-were key features of the program, and facilitated their recovery (Milani et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Previous research found that sense of belongingness predicts attendance and success within 12-step programs (Rice et al, 2012), while "uniqueness" shares operational features with group acceptance, which is considered an important factor for recovery in peer support programs (Repper et al, 2011). Lastly, in a previous study, DDA members reported that acceptance, social identification, and social interaction-which can be conceptualized as uniqueness, belongingness, and inclusion-were key features of the program, and facilitated their recovery (Milani et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…Research suggests peer support groups rely on social ties to aid in recovery from alcohol and substance misuse (Dingle et al, 2019). The process of identification has been found to promote sustained recovery, including within mutual aid groups (Buckingham et al, 2013;Roush et al 2015;Milani et al 2020). As such, the researchers were interested in examining the social ties present within DDA through the lens of inclusion.…”
Section: Feelings Of Inclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same goes for psychosocial interventions and the theories that come with it. In an ontological sense, both substance use and mental disorders are phenomena of such richness that they can be engaged with (potentially effectively) in various ways - through biological intervention, through psychotherapies, through environmental interventions, through social networks as Marijuana Anonymous, Dual Diagnosis Anonymous ( Milani et al, 2020 ) and through policy changes, etc.…”
Section: Discussionmentioning
confidence: 99%